A multi‐site, nurse‐coordinated hepatitis C model of care in primary care and community services in Melbourne, Australia. (29th November 2021) - Harney, Brendan L.; Whitton, Bradley; Paige, Emma; Brereton, Rebecca; Weiss, Robert; Membrey, Dean; Wade, Amanda J.; Iser, David; Kemp, William; Roberts, Stuart K.; Spelman, Tim; Sacks‐Davis, Rachel; et al.
Abstract: Background: Hepatitis C virus (HCV) treatment through primary care and community‐based services will be a critical component of HCV elimination. We evaluated a nurse‐coordinated programme providing care across eight sites and analysed progression through the HCV care cascade. Methods: People‐accessing services from six primary care clinics, a homeless crisis accommodation provider and a mental health service were directly referred to nurses or engaged by nurses during regular clinic visits. Nurses supported HCV testing, treatment and follow‐up. The prescription was provided by affiliated clinicians. Logistic regression was used to examine factors associated with treatment commencement and sustained virological response (SVR) testing. Results: Of 640 people referred to and/or engaged by the nurses from January 2017 to July 2019, 518 had an HCV RNA test of whom 381 (74%) were HCV RNA positive. Treatment was commenced by 281 (74%) people of whom 161 had an SVR test, 157 (97.5%) were cured. Opioid agonist therapy was associated with treatment commencement (aOR 2.68, 95% CI 1.48‐4.88). People who were homeless/unstably housed were less likely to commence treatment (aOR 0.45, 95% CI 0.23‐0.87). Treatment prescription from a specialist (aOR 2.39, 95% CI 1.20‐4.74) and recent injection drug use (<6 months) (aOR 2.15, 95% CI 1.07‐4.31) was associated with SVR testing. Conclusion: A nurse‐coordinated model of care led to high levels of HCV treatment uptake and cure amongst people attending primary care and community services. More tailored models of care may be beneficial for people who are homeless or have unstable housing. These results support primary care and community‐based hepatitis C treatment.